Effects of Simulated Acid Rain Stress on Chlorophyll Fluorescence Characteristics and Growth in Leaves of Lithocarpus glaber and Schima superba Seedlings - Yi, L.T.; Liu, M.H.; Yu, S.Q.; Yu, F.; Yin, X.M. (Asian Journal of Chemistry, 2014)
Acid rain is a serious environmental problem worldwide. Lithocarpus glaber and Schima superba are distributed over large areas in southern China. In this study, the effect of simulated acid rain (SAR) (heavy, pH = 2.5; moderate, pH = 4.0; and control pH = 5.6) on growth, chlorophyll content and leaf chlorophyll fluorescence characteristics of L. glaber and S. superba were investigated. In L. glaber, the leaf relative chlorophyll content (SPAD), the net photosynthetic rate (Pn), the PSII maximum photochemical efficiency (Fv/Fm), actual PSII photochemical quantum yield (FPSII), photochemical quenching (qP), plant height and stem diameter all decreased, when acidity of simulated acid rain increased. Regarding non-photochemical quenching (qN), L. glaber exposed to simulated acid rain had higher value than control plants. However, when exposed to simulated acid rain, SPAD, Pn, Fv/Fm, FPSII, qP, plant height and stem diameter in S. superba seedlings were all in the order of moderate acid rain > control > heavy acid rain, suggesting that moderate acid rain promoted photosynthesis and growth of S. superba to some extent. These results suggest that L. glaber was more sensitive to simulated acid rain than S. superba and provide an insight into the possible mechanisms of the action of acid rain on these two important species in China.